(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-3-178-188 The article represents a try to identify the impact of the journal “On the Rise” in formation literature studying as a component of national fictional literature of the people of North Caucasus. This forms the relevance of this research. The aim of the research is to find out the level of participation of the periodic in creating literary communities in the national regions. The research is conducted on certain historical and comparative-typological analysis of literature phenomena, typological analysis of journal texts. The first national criticists’ articles were published in “On the Rise” and it allows to make a conclusion, that this periodic played a pivotal role in development of literary movement of mountain peoples. This article deals with peculiarities of literature-critic articles, which represent the analysis of the first national writers’ works. Especially, it shows the negative effect on their works of the dictate of writers of proletarian associations who ruled the publishing. It gives a conclusion, that the journal has not fulfilled the requirement on covering the fields of literature widely in the national regions of North Caucasus. Key words: journal “On the Rise”, North Caucasus, national literature, emergence of national literary criticism